Thematic maps for electronic large-scale atlas of experimental farms land use - Kovalchuk, I.; Bogdanets, V. (Land Management, Cadastre and Land Monitoring, 2017)
The article analyzes process and issues of thematic maps compiling for large-scale electronicatlas of land use of university experimental farms. It shows aspects of the practical useof mapped information that reflects the parameters of soils and land quality.Keywords: atlas mapping, GIS mapping, land resources, cartograms, parameters of soil,electronic atlas.